The Effect of Knowledge and Motivation on Nurses’ Attitudes Toward Reporting Patient Safety Incidents at RSU Hermina Opi Jakabaring - Septrianne, Virginia Majestica; Paramarta, Vip; Etty, Etty (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
Patient safety is the foremost priority in healthcare services, with nurses playing a central role in preventing incidents through accurate reporting. However, in practice, patient safety incident reporting often encounters barriers due to limited knowledge and low motivation. This study aims to explain the influence of learning and motivation on nurses’ attitudes toward reporting patient safety incidents, using a descriptive-verificative method, with data collected through questionnaires and analyzed with linear regression. The results indicate that nurses’ knowledge, motivation, and attitudes in carrying out reporting are categorized as good. Knowledge and motivation, both individually and simultaneously, have a positive and significant effect on nurses’ attitudes, indicating that these two variables are crucial factors in strengthening the culture of patient safety incident reporting. Knowledge and motivation serve as key determinants in shaping this reporting culture. Their integration provides both conceptual foundations and consistent practical encouragement, allowing the reporting culture to grow systematically, sustainably, and in support of healthcare quality. This study emphasizes the importance of continuous training and systematic motivational strategies as the foundation for consistent reporting of patient safety incidents, while also suggesting further research on the effectiveness of these interventions in nursing practice.